1
$\begingroup$

Define $\hat{y}=\log\frac{y_t}{y}$ which means percentage deviation from steady state.
Then $\hat{y}=s_c \hat{c}+s_i \hat{i} + s_g \hat{g}$ where $s_c +s_i +s_g =1$.
I can't derive that result.
Is that $\log s_c \approx s_c$?

$\endgroup$
2
$\begingroup$

At every time period, we have: $$ y_t = c_t + i_t + g_t $$ Long run steady state gives: $$ y = c + i + g $$ so, taking differences we have: $$ \begin{align*} &y_t - y = c_t - c + i_t - i + g_t - g,\\ \iff &\frac{y_t - y}{y} = \frac{c}{y}\frac{c_t - c}{c} + \frac{i}{y}\frac{i_t - i}{i}+ \frac{g}{y} \frac{g_t - g}{g} \end{align*} $$ Set $s_c = \dfrac{c}{y}, s_i = \dfrac{i}{y}$ and $s_g = \dfrac{g}{y}$ to be the shares of consumption, investment and government expenditures.

This gives: $$ \frac{y_t - y}{y} = s_c \frac{c_t - c}{c} + s_i \frac{i_t - i}{i} + s_g \frac{g_t - g}{g} $$ Now, we approximate the growth rates. For a variable $x_t$, consider a Taylor expansion of $\ln(x_t)$ around the steady state $x$ $$ \ln(x_t) \approx \ln(x) + \frac{(x_t - x)}{x} $$ This gives $\dfrac{x_t - x}{x} \approx \ln(x_t) - \ln(x) = \ln \dfrac{x_t}{x}$. Substituting gives: $$ \begin{align*} &\ln\frac{y_t}{y} \approx s_c \ln \frac{c_t}{c} + s_i \ln \frac{i_t}{i} + s_g \ln \frac{g_t}{g}.\\ \iff &\hat y = s_c \hat c + s_i \hat i + s_g \hat g. \end{align*} $$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.